THE IMPORTANCE OF EFFECTIVE SCHOOL LEADERSHIP - NDLOVU, BY FRANCIS (IJRDO- Journal of Educational Research, 2017)
The aim of this paper is to provide the rationale for policymakers to invest in school leadership policy. It describes the importance of school leadership and the major challenges faced by school leaders. Effective school leadership is essential to improve teaching and learning within each school and to connect the individual school to the outside world. And yet school leaders across all countries are facing challenges which policymakers need to address. In recent years, the workload of school leaders has expanded and intensified as a result of increased school autonomy and accountability for learning outcomes. As the expectations of what schools should achieve have changed dramatically, schools are seeking to develop new forms of leadership better suited to respond to the needs of rapidly evolving societies. This involves enhancing the capacity of current leaders and preparing and training future leaders.